Physical and mental wellbeing, teaching efficacy and school connectedness - a study with preschool teachers in Portugal - Ferreira, Marco (2024)
This article aims to investigate correlations between physical and mental wellbeing, teaching efficacy and school connectedness and to explore the relationship between those dimensions and sociodemographic variables such as age, teaching experience, academic qualifications, education sector, and geographical regions. For this purpose, an online questionnaire was applied to 450 preschool teachers. To assess physical and mental wellbeing the PISA 2020 teacher questionnaire was used, and to evaluate teaching efficacy and school connectedness the Subjective Teacher Wellbeing Questionnaire was applied. Descriptive statistics were calculated for all variables. The reliability, internal consistency and suitability of the data for factor analysis. were assessed for each of the questionnaires. The ANOVA test and Kruskal–Wallis’s test were used to identify significant differences between the dimensions under analysis and sociodemographic variables. The results show that school connectedness is positively related to teaching efficacy and the same positive association occurs between physical and mental wellbeing. A negative association is observed between school connectedness and physical and mental wellbeing and teaching efficacy and physical wellbeing and mental wellbeing. The results also indicate that older preschool teachers and those with more years of experience had a significantly higher score in teaching efficacy than their younger and less experienced counterparts. The preschool teachers from the Porto and North Regions of Portugal had significantly higher scores in the mental wellbeing dimension when compared with their colleagues from other regions of the country.